Analysis Of Education And Training At Amory Hotel Sumedang - Suci Maulina; Sutopo Sutopo (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2023)
The focus of this research focuses on education and training programs regarding instructors, trainees, methods, materials and training objectives. The purpose of this study was to find out how the implementation of education and training at the Amory Hotel Sumedang and to find out how the efforts to improve education and training at the Amory Hotel Sumedang were. The method used in this research is a descriptive survey with a qualitative approach. In this study, data collection techniques were used, namely interviews and field observations, while the tools for data collection in this study were interviews, observation guidelines, documentation and literature study. So education and training is very important for the ability of employees in a company. Based on the results of interviews and observations made by researchers, there were problems in the implementation of education and training at Amory Hotel Sumedang, indicating that the dimensions of the instructor reflected in the implementation of education and training were quite good but not optimal in motivating participants, the dimensions of the training participants were quite good but not optimal in the desire to pay attention. , the dimensions of the method are good enough, the dimensions of the material are good, and the dimensions of the training objectives are good enough but not optimal in the skills of the participants. Hotel Amory Sumedang to carry out education and training activities more often so that it can have an effect in increasing the abilities and skills of employees at Hotel Amory Sumedang